THE EFFECT OF LISTENING TO MUSIC ON CONCENTRATION AND ACADEMIC PERFORMANCE OF THE STUDENTS: CROSS-SELECTIONAL ON ENGLISH EDUCATION COLLEGE STUDENTS - Meyla Muslimah; Wulan Apriani (Journal of English Teaching, Applied Linguistics and Literatures (JETALL), 2020)
The purpose of this research was to observe and analyze the effect of listening to music while studying to student's concentrate and academic performance. The method of this research uses qualitative methodology the data collection by giving a questionnaire interview, and observation. The object in this research was 24 education college student semester 5 in Universitas Ibn Khaldun in the academic year 2019-2020. The result of this research showed that 18 (75%) of 24 students prefer to listening to music while study meanwhile, 6 (25%) students prefer to do not listen to music while studying. 83,3% of students agree that listening to music while studying can keep their mind calm and it can increase their concentration while studying.